2008
DOI: 10.1094/cchem-85-1-0070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micronutrient Fortification on Nutritional and Other Properties of Nixtamal Tortillas

Abstract: Nixtamalization is the process of steeping dried corn in hot water with calcium hydroxide (lime) with subsequent removal of all or most of the pericarp through washing. The resulting product is called nixtamal. Approximately 60% of corn tortillas in Mexico are produced from nixtamal, with the remainder prepared from nixtamalized corn flour. Nixtamal was fortified with micronutrient premix containing iron, zinc, folic acid, niacin, riboflavin, and thiamin. Premix composition followed a proposed Mexican regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 10 publications
0
34
2
Order By: Relevance
“…This result also agrees well with other studies that show the stability of folate through the baking process. Burton et al (2008) and also found no loss of total folate in the masa during the tortilla baking process. Gujska and Majewska (2005) found a loss of 12-21% of added folic acid but found no loss of endogenous folate during baking for 30-40 min.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This result also agrees well with other studies that show the stability of folate through the baking process. Burton et al (2008) and also found no loss of total folate in the masa during the tortilla baking process. Gujska and Majewska (2005) found a loss of 12-21% of added folic acid but found no loss of endogenous folate during baking for 30-40 min.…”
Section: Resultsmentioning
confidence: 78%
“…One important process variable present in the mill but not in the laboratory was the grinding step. However, Burton et al (2008) also passed fortified nixtamal through volcanic mill stones and observed only a 6% loss of folic acid through the grinding process. No similar process step was used in the laboratory study with CMF.…”
Section: Resultsmentioning
confidence: 99%
“…For most of the foods identified and analyzed, the entire grain component was listed as nonwhole grains. For purposes of this analysis, corn masa flour was considered a non-whole-grain based on its manufacturing process, called nixtamalization-a process that involves steeping dried corn in hot water and exposing it to calcium hydroxide or lime (17). This process hydrolyzes the pericarp and removes it from the grain.…”
Section: Modeling Of Folic Acid Intake From Corn Masa Flourmentioning
confidence: 99%
“…This process hydrolyzes the pericarp and removes it from the grain. The aqueous solution is then drained, and the remaining nixtamal is washed several times, removing seed coats, tip caps, excess lime, and any other impurities (17,18). It was assumed that most identified food products would use corn masa flour as the major flour or grain ingredient, thus making the non-whole-grain component a reasonable proxy.…”
Section: Modeling Of Folic Acid Intake From Corn Masa Flourmentioning
confidence: 99%
“…For the majority of foods identified and analyzed, the entire grain component was listed as non-wholegrain. For the purpose of this analysis, corn masa flour was considered a non-wholegrain based on its manufacturing process, called nixtamalization (22). There were several foods reported in 2003–2004 that were not listed in the MyPyramid Equivalents Database version 2.0 ( n =3); for these foods, the non-whole wheat grain component was estimated using the data from MyPyramid Equivalents Database version 1.0 (2001–2002).…”
Section: Methodsmentioning
confidence: 99%